Mapping of Underwater Seabed Morphology of the Gaza Strip Coastal Zone Using Remote Sensing Technique (2016)
The study investigated the feasibility of applying the depth-invariant index algorithm to delineate the shallow underwater geomorphological features using QuickBird imagery.  Although the technical procedures of the depth invariant index are already demonstrated in the professional literature, the algorithm needs to be applied and tested in several coastal regions with different seawater conditions and properties. Some of the geomorphological features in the coastal zone of the Gaza Strip are seasonal features such as underwater sand bars. However, since these features are non-permanent and dynamic, it would be useful to utilize satellite data to detect changes in both locations and depth, and also to monitor this feature in shallow coastal water. The importance of identifying the underwater sand bars in the coastal zone can be significant in the case of rip currents, and swimming conditions.Additionally, using satellite imagery for detecting dynamic underwater coastal morphologies may enable local authorities to adopt such an algorithm with a combination of satellite imagery for fast, efficient and extensive coverage mapping. While information about seafloor features can be obtained using active satellite data such as RADAR or LiDAR imagery, active satellite data are not available and require advanced processing and logistical resources, which are difficult to obtain in the case of the Gaza Strip. The study instead used passive QuickBirdsatellite imagery to map and delineate the seabed morphologies through the calculating the depth-invariant index for the spectral bands. By using the depth-invariant index, it was possible to distinguish and delineate the major underwater sand bars within the entire coastal zone of the Gaza Strip. Also, the spectral and spatial resolution ofQuickBird imagery exhibited a substantial capability in mapping and delineating the underwater seabed morphologies. ResumenEl estudio investigó la factibilidad de aplicar el algoritmo Índice de Profundidad Invariante para delinear las características geomorfológicas del suelo bajo el agua a través de las imágenes QuickBird. A pesar de que los procedimientos técnicos del Índice de Profundidad Invariante se han demostrado ampliamente en la literatura profesional, el algoritmo debe ser aplicado y verificado en varias regiones costeras con diferentes condiciones y propiedades del agua marina. Algunas de las condiciones geomorfológicas en la zona costera de la Franja de Gaza dependen de las estaciones, como las barreras de arena bajo el agua. Sin embargo, como estas condiciones son dinámicas, sería útil usar la información satelital para detectar cambios en las locaciones y en la profundidad, y para vigilar estas condiciones en el agua costera poco profunda. La importancia de identificar las barreras de arena en la zona costera puede ser determinante en el caso de corrientes violentas o para las condiciones de inmersión. Adicionalmente, el uso de imágenes satelitales para determinar las dinámicas morfológicas costeras bajo el agua podría permitir a las autoridades locales adoptar un algoritmo que combinado con dichas imágenes presente un mapeo más rápido, más eficiente y de mayor cobertura. Si bien la información sobre las características del suelo oceánico pueden obtenerse con información satelital activa como las imágenes de RADAR o LiDAR, la información no está disponible, además de requerir un procesamiento avanzado y recursos logísticos, que son difíciles de obtener en el caso de la Franja de Gaza. Este estudio, por su parte, utiliza imágenes satelitales pasivas de QuickBird para mapear y delinear  las morfologías del lecho del mar a través de calcular el Índice de Profundidad Invariante para las bandas espectrales. Al utilizar el Índice de Profundidad Invariante fue posible determinar y delinear las mayores barreras de arena en toda la costa de la Franja de Gaza. La resolución espacial y espectral de las imágenes de QuickBird mostraron una capacidad sustancial en el mapeo y delineamiento de las morfologías del lecho marino